Evaluation of Dermatological Adverse Drug Reaction in the Outpatient Department of Dermatology at a Tertiary Care Hospital - Gohel, Dimple; Bhatt, Sandip Kumar; Malhotra, Supriya (Indian Journal of Pharmacy Practice)
Background: The burden of dermatological Adverse Drug Reactions (ADRs) is resulting into switching or discontinuation of drug as well as medication non-adherence. Active search is essential for evaluating, managing, reporting ADRs and strengthening the activity of pharmacovigilance of the country. The purpose of the study was to evaluate causality, severity and preventability of Dermatological ADRs. Method: A prospective, observational study was carriedout over a period of six months at Out Patient Department of Dermatology, Sheth V.S. hospital, Ahmedabad with diagnosed dermatological ADRs. The suspected ADRs were evaluated for causality by WHO-UMC causality and Naranjo’s scale, severity by Hartwig and Siegel scale, and preventability by Schumock and Thornton criteria. The agreement between causality scales was obtained by Cohen’s Kappa test. Result: Total of 51 patients were enrolled with 74 suspected ADRs. The incidence of dermatological ADR was 3.78%. Most commonly manifested ADR was rash (26.67%). Total 97 drugs were suspected. Maximum incidence of dermatological ADRs were observed with antimicrobial agents (43.30%) followed by non-steroidal anti- inflammatory drugs (26.80%), possible (54.64%) and 35 (36.08%) probable ADRs by WHO-UMC scale. Naranjo’s scale showed most cases of probable (74.23%). ADRs were of moderate severity (98.97%) and definitely preventable (72.16%). The causality scales showed ‘slight agreement’ with kappa value 0.012. Conclusion: Dermatological adverse drug reactions were a common occurrence and awareness about them was found to be essential for early detection and prevention. The healthcare system can promote the spontaneous reporting of dermatological ADR top Pharmacovigilance centre’s for ensuring safe drug use and patient care.
Keywords: Cutaneous adverse drug reactions; Pharmacovigilance; Epidemiology Ahmedabad